2020
DOI: 10.1371/journal.pone.0227596
|View full text |Cite
|
Sign up to set email alerts
|

Significant changes in synovial fluid microRNAs after high tibial osteotomy in medial compartmental knee osteoarthritis: Identification of potential prognostic biomarkers

Abstract: High tibial osteotomy (HTO) is a well-established treatment for medial compartmental knee osteoarthritis. Several microRNAs (miRNAs) are involved in osteoarthritis progression and are useful as osteoarthritis-related biomarkers. In this prospective study, we investigated differentially expressed microRNAs in the synovial fluid (SF) before and after HTO in patients with medial compartmental knee osteoarthritis to identify microRNAs that can be used as prognostic biomarkers. We used miRNA-PCR arrays to screen fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Numerous studies have reported that mechanical loading causes differential expression of microRNA (MIRNA) in articular cartilage and regulates the levels of matrix-degrading enzymes and inflammatory factors in osteoarthritis cartilage [54]. Specifically, it targets the expression of downstream transcripts.…”
Section: Microrna and Osteoarthritismentioning
confidence: 99%
“…Numerous studies have reported that mechanical loading causes differential expression of microRNA (MIRNA) in articular cartilage and regulates the levels of matrix-degrading enzymes and inflammatory factors in osteoarthritis cartilage [54]. Specifically, it targets the expression of downstream transcripts.…”
Section: Microrna and Osteoarthritismentioning
confidence: 99%
“…Transforming growth factor-β (TGF-β) maintains functions of articular cartilage by transducing Smad2/3 signals, thereby promoting collagen (Col2a1) and fibronectin synthesis and inhibiting ECM degradation induced by overloading ( Madej et al, 2016 ). Mechanical loading also causes differential expression of miRNAs ( Kwak et al, 2020 ) and lncRNAs ( He et al, 2021 ), which regulate the activities of MMPs and the progress of OA development.…”
Section: Discussionmentioning
confidence: 99%
“…This year, advances in single cell technologies were used to profile cell surface markers and disease associated subsets. Recently, Dicks et al were found to be associated with post-operative pain outcomes [35,36]. The identification of these candidates is an important first step, however to have any clinical utility they must be validated in multiple cohorts, with larger sample sizes.…”
Section: Oa Transcriptomics: Examining Phenotypesmentioning
confidence: 99%